Avaliação da qualidade dos serviços das bibliotecas universitárias pelos usuários discentes - Bezerra, Neiliane Alves (2010)
This study focuses on assessing institutional and thematic focus as the subject to evaluate the quality of university libraries, aiming to make a general diagnosis of the quality of university libraries and its association with the outcomes of courses in ENADE, based on the opinions of students . Specifically, it is intended: to determine the degree of user satisfaction with the acquis, its sufficiency and update and check suitability of physical facilities for the users as the air conditioning, lighting and acoustics; check the users' satisfaction in relation to computer equipment available and furniture, knowing the users 'satisfaction regarding attendance and verify the users' satisfaction regarding the opening hours of the library. The literature of the area focuses on the evolution of theories of learning assessment, the various perspectives of the concept of quality in education. Contextualized within the state reforms the development of evaluation systems already deployed by the Brazilian state, highlighting the PAIUB, NEC and National System of Higher Education Assessment (SINAES). Presents a summary of the trajectory of Brazilian university libraries, focusing on the major issues in planning and evaluation. Addresses the management of service quality in university libraries, as well as the relationship between these units of information with academic activities. Contextualizes the study environment, presenting a brief history of the creation of the Federal University of Ceará. The research is exploratory and used as a technical procedure to collect the data field study ex post facto. The sample was chosen on the basis of grades obtained by the courses in ENADE. Data were collected through questionnaire and analyzed using the software Statistical Package for Social Sciences (SPSS), which provided the calculation of measures of location average, median and mode. Through analysis of data revealed that the indicators on which the library had been underperforming for the quantity and availability of computer equipment, furniture and collection service in respect of information needs, the quantity and update. Also showed poor performance critical item on the area for individual study. It is concluded that the quality of the library is related to the quality of training of students, investigated by ENADE.